Humor in Julio Ramón Ribeyro's Short Stories: Consecuence or cause of the Fantastic? - Erwin Snauwaert (Universitat Autònoma de Barcelona, 2018)
Although fantastic narrative and humor increasingly go together –both arise from an incongruity that affects objective reality and pragmatics, respectively–, this combination is not always unambiguous. More specifically, the humorous effect depends on the modality in which the fantastic takes place: in ‘the fantastic of perception’, humor is only a consequence of the clash between the uncanny and everyday life, while in ‘the fantastic of language’ it is incorporated into the enunciation and causes the very fantastic effect. Both modalities are illustrated in some relevant short stories of Julio Ramón Ribeyro. The first occurs in Doblaje, La insigniaand La botella de chicha, where the hero’s confrontation with a disquieting event leads to mere situational humor.  The second is realized by a defective narration in Escena de cazaand El carrusel, or by a suggestive focalization in Sobre las olasand Scorpio, which kindle an absurd humor that triggers the fantastic.